(untitled) (Dubuque, IA, 2008)
From the TAKING SIDES Series, this third edition of TAKING SIDES: SPECIAL EDUCATION presents current controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. Each issue is thoughtfully framed with an issue summary, an issue introduction, and a postscript. An instructor’s manual with testing material is available for each volume. USING TAKING SIDES IN THE CLASSROOM is also an excellent instructor resource with practical suggestions on incorporating this effective approach in the classroom
Keywords: Special education,Special education,Giáo dục đặc biệt; Social aspects